CBP/p300 activation promotes axon growth, sprouting, and synaptic plasticity in chronic experimental spinal cord injury with severe disability. - Franziska Müller; Francesco De Virgiliis; Guiping Kong; Luming Zhou; Elisabeth Serger; Jessica Chadwick; Alexandros Sanchez-Vassopoulos; Akash Kumar Singh; Muthusamy Eswaramoorthy; Tapas K Kundu; Simone Di Giovanni (PLoS Biology, 2022)
The interruption of spinal circuitry following spinal cord injury (SCI) disrupts neural activity and is followed by a failure to mount an effective regenerative response resulting in permanent neurological disability. Functional recovery requires the enhancement of axonal and synaptic plasticity of spared as well as injured fibres, which need to sprout and/or regenerate to form new connections. Here, we have investigated whether the epigenetic stimulation of the regenerative gene expression program can overcome the current inability to promote neurological recovery in chronic SCI with severe disability. We delivered the CBP/p300 activator CSP-TTK21 or vehicle CSP weekly between week 12 and 22 following a transection model of SCI in mice housed in an enriched environment. Data analysis showed that CSP-TTK21 enhanced classical regenerative signalling in dorsal root ganglia sensory but not cortical motor neurons, stimulated motor and sensory axon growth, sprouting, and synaptic plasticity, but failed to promote neurological sensorimotor recovery. This work provides direct evidence that clinically suitable pharmacological CBP/p300 activation can promote the expression of regeneration-associated genes and axonal growth in a chronic SCI with severe neurological disability.